Evaluation Of Readiness for Implementing IFRS S1 and S2 in Accordance with the Sustainable Stock Exchange Guidelines: A Case Study at PT X - Tashya Fitriani Modjaningrum; Ancella A. Hermawan (Eduvest - Journal of Universal Studies, 2025)
The launch of the new sustainability standards by the ISSB, namely IFRS S1 and S2, marks a major advancement in sustainability reporting, enabling companies to use a unified standard for sustainability information. These standards differ from Global Reporting Initiative (GRI) Standards by focusing on sustainability and climate-related risks and opportunities, which creates information gaps in current company disclosures. This study evaluates readiness for implementing these standards. Using value chain theory and the resource-based view (RBV), the study maps all business process activities. A qualitative case study involving interviews with company management, sustainability reports, and internal documents applies data triangulation to identify disclosure gaps. Findings reveal many supporting activities remain undisclosed, and sustainability disclosures do not yet align with GRI due to limited understanding of the company’s value chain. Gap analysis with IFRS S1 and S2 shows the largest discrepancies in metrics and targets related to sustainability risks, opportunities, and climate change. Operational activities outside the value chain—such as IT maintenance, business meetings, and travel—are notably excluded. Emissions and energy use from these activities remain uncalculated and undisclosed. The study concludes that enhancing sustainability disclosures requires accurately mapping the value chain and incorporating all operational activities from upstream to downstream. This comprehensive approach will enable successful implementation of IFRS S1 and S2 at the company.